THE INFLUENCE OF PERCEIVED EASE OF USE, PERCEIVED USEFULNESS AND TRUST ON REPURCHASE INTENTION OF LION AIR E-TICKET - Oroh, Cindy Regina; Rumokoy, Farlane S. (FEB Universitas Sam Ratulangi Manado, 2015)
The development function of internet has shown the crucial impact on the changing behavior of consumer where consumer perception of internet not only as communication medium but also becomes transaction medium. It was also shown the influence in Airline Industry that can be seen on from the advanced of e-ticket. Lion Air was known as private airline company that adopted e-ticket to provide easier way of purchasing that useful and trusted. The purpose of this research is to know the influence of perceived ease of use, perceived usefulness and trust partially and simultaneously. Data collection method used purposive sampling technique. Sample of 100 questionnaires were distributed to customer of Lion Air in Manado, and multiple regression analysis is used. This research results shows simultaneously influence of perceived ease of use, perceived usefulness and trust on repurchase intention of Lion Air E-ticket. While, partially only trust shows significant influence on repurchase intention of Lion Air E-ticket. Lion Air management should provide electronic tickets for flights in transit, to improve the ease of purchase and provide benefits for the company. Keywords: perceived ease,usefulness, trust, repurchase intention